(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Apoptosis of trophoblastic cells may play a role in the pathogenesis of abortion, and one mechanism of apoptosis is Fas receptor and legand system. Objective:Estimate the level of Fas and FasL in trophoblastic tissue of aborted women. Methods: In this study, 25 women with spontaneous abortion and 5 women with induced abortion were included from attendants of Gynecology department at Al-Kadhimiya Teaching Hospital in Baghdad. In-situ hybridization (ISH) tests were done to detect the level of expression of Fas and FasL in trophoblastic tissue. Results:The highest percentage of expression of Fas and FasL was found in the trophoblastic tissue of females with spontaneous abortion (34.36% for Fas and 31.86% for FasL), while the expression of them was low in induced abortion group (9.2% and 9.4%, respectively). Conclusion:The data strengthen the possibility that the apoptosis of trophoblastic cells via enhanced expression of Fas-FasL system is an important mechanism of spontaneous abortion. Key words:Miscarriage, Trophblast, Apoptosis, Fas, FasL, ISH.